Pembentukan Titanium Nitrida (TiN) dengan Proses Nitriding pada Titanium Murni Menggunakan Plasma Densitas Tinggi - Windajanti, Josephine Maria; Santjojo, Dionysius Joseph Djoko Herry; Abdurrouf, Abdurrouf (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2017)
Pure titanium has been widely utilized in industry but its products suffered from low wear and erosion resistance. The plasma nitriding was selected as a tool to harden the pure titanium products but typically high temperature processing was required to attain high hardness. In the present study, high density plasma nitriding system was applied to make low temperature plasma nitriding at 723 K (or 450Â°C) for 14.4 ks (or 4 hours).Â The average measured hardness reached to 624 HV.Â This high hardness of plasma-nitrided pure titanium at low temperature was attributed to formation of fine TiN precipitates and nitrogen solid solution into vacancy sites in the HCP crystalline structure of titanium.